Are Fluctuations in Coal Consumption Transitory or Permanent? Evidence from A Panel of US States - Apergis, Nicholas; Loomis, D.; Payne, J. (Elsevier, 2010)
This short communication investigates whether or not US coal consumption follows a stationary process by examining coal consumption for the 50 US states over the period 1982–2007. Employing several panel unit root and stationarity tests with endogenously determined structural breaks, the results indicate that coal consumption is integrated of order zero. Thus, energy conservation policies oriented towards the reduction of coal consumption will only have short-term effects.